2020
DOI: 10.20546/ijcmas.2020.911.126
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable In-situ Jute Retting Technology in Low Volume Water using Native Microbial Culture to Improve Fibre Quality and Retting Waste Management

Abstract: Jute (Corchorus olitorius L.) is the cheapest natural industrial fibre of great economic importance to South Asian countries. The final important management step of a wellraised jute crop is the process of separation and extraction of fibres from the bast layer of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…For life saving irrigations using surface water, an insitu micro pond (120 m 2 only with a depth of 1.5 m) has to be dug out in 1/3 rd of an acre (1333 m 2 ) sacrificing 9 percent of its area at the lowest corner of the field to harvest rain water. It can collect runoff water up to 1,80,000 litres of water or even more if the dugout soil is used for making embankment over it (Photo 4, [20,21]. At ICAR-CRIJAF, Kolkata, in last week of June (2010), it was observed that runoff collection from one 30 mm rain from 1/3 rd an acre was 60000 litres of water in such dug out insitu ponds.…”
Section: Life Saving Water From Rain Water Harvesting In Insitu Micro...mentioning
confidence: 99%
“…For life saving irrigations using surface water, an insitu micro pond (120 m 2 only with a depth of 1.5 m) has to be dug out in 1/3 rd of an acre (1333 m 2 ) sacrificing 9 percent of its area at the lowest corner of the field to harvest rain water. It can collect runoff water up to 1,80,000 litres of water or even more if the dugout soil is used for making embankment over it (Photo 4, [20,21]. At ICAR-CRIJAF, Kolkata, in last week of June (2010), it was observed that runoff collection from one 30 mm rain from 1/3 rd an acre was 60000 litres of water in such dug out insitu ponds.…”
Section: Life Saving Water From Rain Water Harvesting In Insitu Micro...mentioning
confidence: 99%
“…However, while flushing the body of water, sedimented pollutants are reintroduced into the body of water, causing two secondary pollutions, affecting the water bodies of the downstream basins and causing specific pollution in the downstream water bodies. On this basis, due to the introduction of a large amount of new water into the water body, the original river water level rise is very likely to cause the river to divert, and the project cost is huge, which further shows that this method cannot solve the fundamental problem [18,19].…”
Section: Water Diversion and Pollution Flushing Technologymentioning
confidence: 99%
“…The decomposition of the parenchymatous tissues proceeds due to microbial enzyme secretion (Haque et al 2001). In recent years, microbial consortium approaches have been highly used to shorten the retting time and to upgrade the retting and fiber quality (Ghorai and Chakraborty 2020). Water absorption and liberation of soluble constituents like sugar, glucosides, and nitrogenous compounds from jute plants favor initial microbial growth.…”
Section: Introductionmentioning
confidence: 99%